2014
DOI: 10.33762/bvetr.2014.88136
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Molecular Detection of Pasteurella Multocida in Outbreak of Respiratory Tract Infection of Sheep and Goats in Basrah Province

Abstract: One hundred eight nasal swabs and blood samples from respiratory tract infected animals 66 from sheep and 52 from goats were collected from different sites of Basrah province during a period from December 2012 to April 2013 for isolation and identification of the Pasteurella multocida according to PCR assay . Nasal swabs and blood samples were directly cultured on proper media, then five colonies from the agar plate of suspected P. multocida cultures were used for extracted DNA and, further used for Polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…This is in line with the findings of Alemneh and Tewodros [ 4 ]. However, the results of this study were lower than those reported by Rasha et al [ 41 ], who reported pasteurella species from sheep and goats with a recovery rate of 56% and 44%, respectively. Also, this finding was higher than the finding obtained by Alemneh and Tewodros [ 4 ], who reported 37.1% and 21.9% prevalence in sheep and goats, respectively.…”
Section: Discussioncontrasting
confidence: 96%
“…This is in line with the findings of Alemneh and Tewodros [ 4 ]. However, the results of this study were lower than those reported by Rasha et al [ 41 ], who reported pasteurella species from sheep and goats with a recovery rate of 56% and 44%, respectively. Also, this finding was higher than the finding obtained by Alemneh and Tewodros [ 4 ], who reported 37.1% and 21.9% prevalence in sheep and goats, respectively.…”
Section: Discussioncontrasting
confidence: 96%
“…of affected lungs from goat. In Iraq, Pasteurella multocida was found in 4% and Mannheimia haemolytica in 2.6% (Ahmed et al, 2023), 31.4% (Assefa et al, 2018), 21.9% (Alemneh et al, 2016), 36.5% of goats and in 56% of sheep (Rasha et al, 2014). Pneumonic pasteurellosis has been reported in Bangladesh by many investigators where Pasteurella spp.…”
Section: Prevalence Ratementioning
confidence: 99%